Fundamentals of the multi-variant system for the optimization of technological processes - Todić, Velimir; Banjac, Dragan (Journal of Production Engineering, 1984)
Techno-economic optimization of the technological process has always proved to be a powerful solution for testing the production process and rationalizing the production preparation. In this paper the basics of the variant system of optimization of technological processes are presented, which is based on developed models of internal optimization.